An Analysis of Compound Words in English Captions of the British Embassy’s Instagram Account (@ukinindonesia) - Jawi Sundari; Sri Wahyuni (English Education Journal, 2024)
The primary goal of this research is to determine the writing forms and functions of compound terms discovered in English captions from the British Embassy in Indonesia's official Instagram account, @ukinindonesia. The data in this study was analyzed using a descriptive qualitative approach with document analysis. The theory from Akmaijan (2010) is used to determine the writing formation of a compound word in an English caption, whereas McCarthy's (2002) theory is used to determine the type of function of compound words. The findings of this analysis reveal that there are 120 compound terms in the English caption of the British Embassy's account @ukinindonesia. From the writing perspective, single-form compound words are the most used compared to the separated compounds. The hyphenated compound is the least used because the compound is not so commonly used in the making or writing captions containing compound words in English, and the captions on the account are mostly written in a simple, understandable way. The three functions of compound words are compound nouns, compound adjectives, and compound verbs. The account of the British Embassy mostly used compound nouns rather than compound adjectives and compound verbs, because compound nouns are the easiest compound to create and apply in making sentences and caption under the post. Based on the data found in this study, the compound words used in the English captions of the British account @ukinindonesia on Instagram are varied, rich, and unique, and play a vital role in delivering information and engaging with its followers on Instagram.